The Relationship Between Likelihood and Fear of Criminal Victimization : Evaluating Risk Sensitivity as a Mediating Concept - Austen, Liz; Ditton, Jason (The British journal of criminology, 2007)
Crime surveys typically ask respondents how likely' they think it is that they will become a crime victim in the future. The responses are interpreted here as risk' statements. An investigation of the risk literature shows the concept to be considerably more complex than at first imagined, but shows that individual risk predictions are largely based on interpretations far removed from rational considerations of likelihood based on recorded crime rates. Responses from three waves of a longitudinal crime survey conducted in Trinidad are examined in this light. It is concluded that fear of criminal victimization might best be considered as differential sensitivity to predicted risk